The future prospect of PV and CSP solar technologies: An expert elicitation survey - Valentina Bosetti; Michela Catenacci; Giulia Fiorese; Elena Verdolini (Fondazione Eni Enrico Mattei (FEEM), 2012)
In this paper we present and discuss the results of an expert elicitation survey on solar technologies. Sixteen leading European experts from the academic world, the private sector and international institutions took part in this expert elicitation survey on Photovoltaic (PV) and Concentrated Solar Power (CSP) technologies. The survey collected probabilistic information on (1) how Research, Development and Demonstration (RD&D) investments will impact the future costs of solar technologies and (2) the potential for solar technology deployment both in OECD and non-OECD countries. Understanding the technological progress and the potential of solar PV and CPS technologies is crucial to draft appropriate energy policies. The results presented in this paper are thus relevant for the policy making process and can be used as better input data in integrated assessment and energy models.
Keywords: Q42; Q55; 330; Expert Elicitation; Research; Development and Demonstration; Solar Technologies